Display of hepatitis B virus 'a' determinant on the surface of Macrobrachium rosenbergii (de Man, 1879) nodavirus-like particle capsid protein - Nyakaat, Ninyio Nathaniel (2020)
Complications resulting from hepatitis B account for ~1.45 million deaths each year. To date, none of the available treatments is curative and the prophylactic hepatitis B vaccines can only protect ~90% of vaccinated individuals. Other limitations of current vaccination include poor immunogenicity in people with pre-existing conditions and people with unresponsiveness to yeast-derived vaccines. Overall, this necessitates the continuous development of novel hepatitis B vaccines with improved efficacy. This study is aimed at developing a novel hepatitis B vaccine candidate by producing a chimeric virus-like particle (VLP) displaying the hepatitis B virus (HBV) ‘a’ determinant (aD). The aD is the immuno-dominant region of HBV that induces the production of HBV-neutralising antibodies during infection. Furthermore, aD is conserved among different strains of HBV making it suitable for use in the development of HBV vaccines. In this study, the aD was fused to the C-terminus of the Macrobrachium rosenbergii nodavirus (MrNV) capsid protein (Nc) and expressed in Spodoptera frugiperda (Sf9) cells. SDS-PAGE analysis showed that the expressed protein was ~52 kDa in size. Subsequently, dynamic light scattering (DLS) analysis revealed that the recombinant Nc-aD protein assembled into heterogeneous particles ranging from ~23.4 to ~58.0 nm in diameter. Also, transmission electron microscopy (TEM) confirmed that these particles were spiky spherical virus-like particles (VLPs) with a diameter ranging from ~21 to ~55 nm. Circular dichroism (CD) spectroscopy further revealed that these Nc-aD VLPs consisted of β-sheets (44.8%), random coils (38.7%), a-helices (16.1%) and B-turns (0.3%) with a melting temperature (Tm) of ~56.2 C. Furthermore, enzyme-linked immunosorbent assay (ELISA) of these Nc-aD VLPs revealed that the aD was significantly antigenic when probed with the antihepatitis B surface antigen (HBsAg) monoclonal antibody. Subcutaneous immunisation of BALB/c mice with three doses of these purified Nc-aD VLPs (100 μL; 0.34 mg/mL) elicited a robust humoral immune response that was sustained for 126 days. The elicited humoral immune response was significantly higher (p<0.001) than those elicited by a commercially available hepatitis B vaccine and those of Escherichia coli-produced Nc-aD. In addition, immunophenotyping showed that the Sf9-produced Nc-aD VLPs induced an increase of cytotoxic T-lymphocytes (CTL) (0.65 CD8+/CD4+ ratio) and NK1.1 natural killer cells (13.8%). Memory B cell enzyme-linked immunospot (ELISPOT) analysis was performed 126 days after the administration of the second booster injection. The analysis showed the presence of aD-specific antibody-secreting memory B cells in polyclonally activated mice splenocytes (26.67 spots). The significant humoral, CTL, natural killer cell and memory B cell immune responses induced by these Sf9-produced Nc-aD VLPs suggest that this recombinant protein presents good prospects for use as a hepatitis B vaccine candidate.